A case report of discordant Chikungunya manifestations in a married couple: From acute undifferentiated fever to fatal sepsis with purpura fulminans - Ditthawat Pathomchareansukchai; Navin Horthongkham; Pinyo Rattanaumpawan (IDCases)
Chikungunya virus, an alphavirus transmitted by mosquitoes, causes chikungunya fever, a non-fatal febrile illness characterized by severe arthralgia and rash. We are reporting on two Chikungunya cases who recently returned from the Thailand-Cambodia border. The first case involved a man who presented with atypical manifestations, including purpura fulminans and multi-organ failure, ultimately leading to death. Conversely, the subsequent case pertains to the spouse of the deceased, who exhibited typical symptoms.